The practice of public engagement on projects: from managing external stakeholders to facilitating active contributors - Vivien Chow; Roine Leiringer (2019)
The premise of public engagement is to invite community members into the project’s decision-making processes. In project management research, public engagement is usually addressed under the umbrella of stakeholder management, which, although a useful perspective to adopt, has its limitations. In this article, a processual view is advocated, which treats public engagement as dynamic and emergent. Drawing on ethnographic data, we demonstrate how observing public engagement “in the making” helps explain the politics behind engagement efforts. This allows for conclusions to be drawn about the practice of engagement that reflects the evolving needs of stakeholders and how best to manage them.